OPTIMIZING POPULATION ADMINISTRATION SERVICES IN RURAL AREAS: A STUDY OF DIGITAL INTEGRATION AND BUREAUCRATIC RESPONSIVENESS IN BUNGA VILLAGE - Sri Wahyuni Ismail; Mohamad Ikbal Kadir; Ikram Muhammad (LP2M Universitas Bina Mandiri Gorontalo, 2024)
Population administration is a fundamental public service that ensures citizens' legal identity and access to social protection. This study aims to evaluate the implementation of population administration services in Bunga Village, Bone Raya Sub-district, Bone Bolango Regency, focusing on the integration of the Population Administration Information System (SIAK) and the quality of frontline service delivery. Using a qualitative descriptive approach, data were collected through in-depth interviews with village officials and community members, field observations, and documentary analysis. The findings reveal that Bunga Village has successfully modernized its administrative workflow through SIAK, enhancing data accuracy and processing efficiency. A key highlight is the village's